Synthesis of poly(3-hexylthiophene) active layer with ZnO nanorods and AU nanoparticles for the fabrication of hybrid plasmonic solar cells - González Pérez, Adela Verónica (2019)
Purpose and method of study: In the present study, zinc oxide nanobars were synthesized by electrochemical method and poly(3-hexylthiophene) by template-assisted method, as well as gold nanoparticles by microwave. The three components were incorporated as part of a hybrid plasmonic solar cell, in two configurations: inverted ITO/ZnO/P3HT/Au and conventional ITO/P3HT/ZnO/Au. The nanobars and nanoparticles were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, UV-Vis spectroscopy and dynamic light scattering. The solar cells were characterized with the use of a solar simulator and a picoammeter. Conclusions and contributions: A methodology was developed to adhere polymer nanorods, vertically aligned, on ITO glass; subsequently, ZnO nanobars were formed on the polymer matrix. Two hybrid plasmonic solar cells were fabricated in which gold nanoparticles were used as cathode; the nanoparticles were incorporated into the hybrid layer of ZnO and P3HT by electrophoretic deposition, which is presented as an alternative to the deposit of conductive metals by thermal evaporation. The basic parameters of the conventional solar cell were Voc = 200 mV, Jsc = 1.09x10-7 mA/cm2 , FF of 30%, while those of the inverted solar cell were Voc = 400 mV, Jsc = 6.95x10- 8 mA/cm2 , FF of 28%, however, the efficiencies of both were null (in the order of 10-7), due to the little contact between the different components of the cell.